Genetic Polymorphisms in XRCC1, CD3EAP, PPP1R13L, XPB, XPC, and XPF and the Risk of Chronic Benzene Poisoning in a Chinese Occupational Population. - Ping Xue; Lin Gao; Sha Xiao; Guopei Zhang; Mingyang Xiao; Qianye Zhang; Xiao Zheng; Yuan Cai; Cuihong Jin; Jinghua Yang; Shengwen Wu; Xiaobo Lu (PLoS ONE)
Objectives Individual variations in the capacity of DNA repair machinery to relieve benzene-induced DNA damage may be the key to developing chronic benzene poisoning (CBP), an increasingly prevalent occupational disease in China. ERCC1 (Excision repair cross complementation group 1) is located on chromosome 19q13.2-3 and participates in the crucial steps of Nucleotide Excision Repair (NER); moreover, we determined that one of its polymorphisms, ERCC1 rs11615, is a biomarker for CBP susceptibility in our previous report. Our aim is to further explore the deeper association between some genetic variations related to ERCC1 polymorphisms and CBP risk. Methods Nine single nucleotide polymorphisms (SNPs) of XRCC1 (X-ray repair cross-complementing 1), CD3EAP (CD3e molecule, epsilon associated protein), PPP1R13L (protein phosphatase 1, regulatory subunit 13 like), XPB (Xeroderma pigmentosum group B), XPC (Xeroderma pigmentosum group C) and XPF (Xeroderma pigmentosum group F) were genotyped by the Snapshot and TaqMan-MGB® probe techniques, in a study involving 102 CBP patients and 204 controls. The potential interactions between these SNPs and lifestyle factors, such as smoking and drinking, were assessed using a stratified analysis. Results An XRCC1 allele, rs25487, was related to a higher risk of CBP (P<0.001) even after stratifying for potential confounders. Carriers of the TT genotype of XRCC1 rs1799782 who were alcohol drinkers (OR = 8.000; 95% CI: 1.316-48.645; P = 0.022), male (OR = 9.333; 95% CI: 1.593-54.672; P = 0.019), and had an exposure of ≤12 years (OR = 2.612; 95% CI: 1.048-6.510; P = 0.035) had an increased risk of CBP. However, the T allele in PPP1R13L rs1005165 (P<0.05) and the GA allele in CD3EAP rs967591 (OR = 0.162; 95% CI: 0039~0.666; P = 0.037) decreased the risk of CBP in men. The haplotype analysis of XRCC1 indicated that XRCC1 rs25487A, rs25489G and rs1799782T (OR = 15.469; 95% CI: 5.536-43.225; P<0.001) were associated with a high risk of CBP. Conclusions The findings showed that the rs25487 and rs1799782 polymorphisms of XRCC1 may contribute to an individual's susceptibility to CBP and may be used as valid biomarkers. Overall, the genes on chromosome 19q13.2-3 may have a special significance in the development of CBP in occupationally exposed Chinese populations.